The Role of Change Leadership in Developing a Local Community-Based Spirit of Literacy in the Cirebon Reading Community - Fajar Syaifurrochman; Sri Almiyah; Diva Puspa Afshari; Mega Purnamasari (Politeknik Siber Cerdika Internasional, 2026)
Literacy is an important foundation for human resource development and social development. However, various local literacy communities face sustainability challenges due to limited resources and member participation dynamics. This study aims to analyze the role of change leadership in fostering a spirit of local community-based literacy in the Cirebon Reading Grow Reading Community. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and documentation studies. Research informants included community activists, core administrators, and active members. Data analysis was conducted using an interactive analysis model that included data reduction, data presentation, and conclusion drawing. Its validity was tested through triangulation of sources and techniques. The results show that change leadership plays a crucial role in building a shared literacy vision, encouraging literacy program adaptation, empowering members, and managing resistance to change. This change leadership impacts increased member participation, consistency of literacy activities, and the formation of collective literacy awareness. This study concludes that change leadership is a key factor in maintaining the sustainability and strengthening of local community-based literacy movements.